Generalization of Data Science in Financial Management - Wu, Yuxia; Zhang, Hao (LPPM STIKI Malang, 2024)
With the rapid development of information technology, data science has been increasingly applied in various fields, and financial management is no exception. As a comprehensive discipline, data science brings new opportunities and challenges to financial management through its powerful data processing and analyzing capabilities. The purpose of this paper is to explore the ubiquity of data science in financial management, and to analyze its impact on financial management and future development trends.